Facilitating women’s access to an economic empowerment initiative: Evidence from Uganda - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (Elsevier, 2021)
We study the take‐up of an intervention designed to increase women’s economic empowerment among sugarcane farmers in Uganda. We find that lower socioeconomic status and household gender norms both predict a couple’s refusal of the intervention. We also randomly assign couples to a workshop that aims to increase communication and gender balance in the household and find that couples invited to the workshop were less likely to refuse the subsequently offered empowerment intervention. Moreover, the workshop was effective at addressing sources of disadvantage that arise from household gender norms and division of labor, and less effective at addressing refusal rates associated with socioeconomic status.